2021
DOI: 10.1039/d1cs90042k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Mechanochemical tools for polymer materials

Abstract: Correction for ‘Mechanochemical tools for polymer materials’ by Yinjun Chen et al., Chem. Soc. Rev., 2021, 50, 4100–4140, DOI: 10.1039/D0CS00940G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…28,29 Mechanophores creating radicals are subjected to homolytic cleavage, whereas the term heterolytic is conventionally invoked when charged species are generated. 1,30 All these descriptions are compatible with both scissile and non-scissile pathways. This Synpacts contribution focuses on heterolytic cleavage, hence the scissile/non-scissile distinction will be further elaborated for reactions that fall under the heterolytic category.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…28,29 Mechanophores creating radicals are subjected to homolytic cleavage, whereas the term heterolytic is conventionally invoked when charged species are generated. 1,30 All these descriptions are compatible with both scissile and non-scissile pathways. This Synpacts contribution focuses on heterolytic cleavage, hence the scissile/non-scissile distinction will be further elaborated for reactions that fall under the heterolytic category.…”
Section: Introductionsupporting
confidence: 52%
“…Mechanophores can be defined as chemical species that provide physico-chemical responses as consequence of force-induced transformations. [1][2][3][4][5] The term was coined less than two decades ago, 6 and it quickly established itself due to the general scientific interest raised by the rise of polymer mechanochemistry. [7][8][9][10][11][12] Although the definition of mechanophore previously offered is rather general, the most common practical scenario involving mechanophores consists in small molecules containing so-called weak chemical bonds -linkages that are mechanically labileembedded in polymeric architectures (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than ten review articles concerning polymer mechanochemistry have been published. These reviews have mainly focused on i) design and evaluation of mechanophore-embedded polymers, 34 35 36 37 38 39 ii) methods for mechanical activation of responsive polymers, 40–44 and iii) similarities and differences between various computational tools for mechanochemical research. 45,46 A comprehensive review of the role of heterocyclic structures as mechanophores in polymer mechanochemistry would be beneficial for the field, but such a review has not been done yet.…”
Section: Introductionmentioning
confidence: 99%
“…The transmittance of the hydrogels has nonnegligible effect on the quantitative analysis of their mechanochemiluminescence. 29 UV/Vis transmittance spectra of the swelling hydrogels ( Figure 1a ) showed that they had similar transmittance, which was essential for quantitative analysis of luminescence intensity. In contrast, an alternative, one-pot preparation method (Table S1) resulted in distinctly decreased transmittance values for hydrogels with water content higher than 50% (Figure S5), which might be caused by the formation of big micelles in large amount of water from DLS measurement results (Figure S6).…”
mentioning
confidence: 99%